Penerapan Teknologi Biodekomposer Trichoderma Berbasis Limbah Pertanian Di Kelompok Tani Tontong Suit - Prasetyowati, Rini Endang; Ningsih, Dwi Haryati; Wadi, Ikhwan (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2025)
The Tontong Suit Farmers Group is a group of farmers formed based on shared interests and a shared understanding of the group's business development. Located in Bagik Papan Village, Pringgabaya District, East Lombok Regency, the group has abundant local raw material resources, including corn cob waste and goat manure. Partners' main challenges include underutilization of abundant agricultural waste, rising prices of non- subsidized chemical fertilizers, and low technical knowledge and skills related to the use of high-quality trichoderma biodecomposers. Therefore, the purpose of the community service is to improve the understanding and skills of farmer group members using agricultural waste-based trichoderma biodecomposers. The implementation stages of community service activities include observation, problem identification, developing action plans, evaluation and follow-up. The results obtained are an increase in knowledge and technical skills of farmer group members utilizing agricultural waste-based trichoderma biodecomposers. The enthusiasm and feedback from participants are important points that are useful for the program's follow-up, namely mentoring the provision of compost fertilizer with trichoderma biodecomposers to each member of the Tontong Suit farmer group, with the hope that farmers can apply trichokompos in their farming activities, thereby increasing production and farmer income.